EVALUATION OF THE APPLICABILITY OF THE O.K.N.V.I. RESIST-5 AND THE KPC&MBL&0XA-48 DISK TESTS IN A ROUTINE MICROBIOLOGY LABORATORY - Stefana Sabtcheva; Sylvia Georgieva (Problems of Infectious and Parasitic Diseases)
Background: The global spread of carbapenemase-producing Enterobacterales (CPE) and the increasing emergence of clinical Enterobacterales harboring multiple carbapenemases of different molecular classes have prioritized the use of rapid molecular detection methods in routine microbiology laboratories. The aim of this study was to evaluate the applicability of the immunochromatographic O. K.N.V.I. RESIST-5 and the KPC&MBL&0XA-48 disc tests in a clinical microbiology laboratory.